Clinical, Pathological and Immunohistochemical Evaluation of a Primary Hemangiosarcoma in a Pinscher Dog - Anjos, Denner Santos dos; Assis, Andreia Regis; Fonseca-Alves, Carlos Eduardo [UNESP]; Babo-Terra, Veronica Jorge (Univ Fed Rio Grande Do Sul, 2016)
Background: Hemangiosarcoma (HSA) is a malignant tumor that arises from the vascular endothelium affecting more often dogs than other species as cats, cows and horses. It comprises approximately 2% of all tumors in dogs. The most common primary site for the HSA in dogs is the spleen, and other locations include the right atrium, pericardium, liver and prostate. Other authors have reported this tumor in lungs, kidney, oral cavity, muscle, bone, urinary bladder, left ventricle, tongue and retroperitoneum. Due to the importance of the HSA in canine species, the aim of this study was to describe the clinical and pathological findings, besides therapeutic protocol in an unusual case of HSA. Case: A six-year-old male pinscher was referred to the veterinary hospital with a history of cyanosis and choking. The animal was submitted to radiographic examination in lateral cervical view, which identified the presence of a mass of 1.2 cm in diameter near the pharynx. In order to evaluate the oral cavity, general anesthesia was performed, and it was possible to see a soft, rosy, circumscribed and vascularized lump in pharyngeal region. Due to suspicion of neoplasm, excisional biopsy without surgical margin was performed. The histopathological exam diagnosed hemangiosarcoma. Immunohistochemistry against vimentin, factor VIII, VEGF and Ki67 was performed and confirmed diagnosis of low grade hemangiosarcoma. Antineoplastic chemotherapy protocol was initiated with doxorubicin and cyclophosphamide every 21 days totaling six sessions. However, the animal died after the cyclophosphamide intoxication with a three-fold recommended dose (660 mg/m(2) total in the last session), showing a median survival rate of 220 days. Discussion: The most common primary site for HSA in dogs is the spleen. The pharyngeal location is rare, with only a few reports in literature. In the present case, solitary tumor was observed in pharynx with no involvement of other organs, evidenced by radiographic examination, abdominal ultrasound and echocardiogram, suggesting that pharynx was the primary location of the tumor. Main features of HSA comprise a solitary nodule or multifocal lesions within the organ or widely disseminated. Histologically, they consist of pleomorphic immature endothelial cells with formation of vascular spaces with variable amount of blood and/or thrombi. In some cases, HSA shows a polymorphic subtype and immunohistochemistry is necessary to provide a definitive diagnosis. The sample was submitted to histopathological examination which revealed proliferation of endothelial cells with pronounced pleomorphism ranging from polygonals to ovoid, sparse cytoplasm, round to oval nucleus with visible nucleolus, few mitotic figures, some of them, aberrant, which confirmed diagnosis of HAS. Due to the unusual location, we performed immunohistochemical staining for vimentin, factor VIII, VEGF and Ki67 antibodies to confirm mesenchymal origin of the tumor. In IHC, it was possible to identify positive reaction for vimentin protein, factor VIII, VEGF and few Ki67 positive cells, confirming histopathological diagnosis. Despite literature describes an aggressive biological behavior of canine HSA, with common occurrence of metastasis, recurrence was not observed at the site of the removal of the tumor. In histopathological evaluation, it was observed low number of mitoses, besides the low Ki67 expression on IHC, featuring a low grade tumor with minor ability to metastasize. To the author's knowledge, this case describes an unusual presentation of HSA, with low metastatic potential, in which chemotherapy protocol achieved survival time of 220 days.
Keywords: angiosarcoma; dogs; immunohistochemistry; pharynx